Strategy for Increasing the Number of Customers in Sharia Banks - Nasution, Mutiara Akbar; Fitri, Anisa; Lubis, Cinta Rizkia Zahra; Nabila, Zada Annuri; Safitri, Nurdina (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study aims to discuss strategies in increasing the number of customers in Islamic banks. This study uses a qualitative method with a literature study approach, which involves collecting data from various sources such as journals and related articles. The results of the study indicate that there are several strategies that can be applied by Islamic banks to increase the number of their customers, including optimal use of technology, use of Islamic fintech, promotion through various media channels, and mergers or consolidations with other banks. In addition, this study also identifies challenges faced in implementing Islamic bank marketing strategies, such as the lack of public understanding of Islamic banks and the lack of quality human resources in the field of Islamic banking.